Electromagnetic Radiation‐Based Dry Blanching of Red Bell Peppers: A Comparative Study. Issue 5 (9th September 2013) - Jeevitha, G.C.; Hebbar, H. Umesh; Raghavarao, K.S.M.S.
Abstract Retention of water‐soluble nutrients, prevention of solid loss and elimination of waste water generation are some of the advantages of dry blanching. Dry blanching of red bell pepper (Capsicum annuum L.) slices using infrared (IR) and microwave (MW) radiations was attempted and its performance was compared with conventional water and steam blanching methods. Processing conditions (time and temperature) were standardized on the basis of degree of enzyme inactivation (peroxidase, polyphenol oxidase). Effect of blanching methods on retention of micronutrients such as ascorbic acid, β‐carotene and protein, besides product shrinkage, structure and texture (shearing force) were analyzed. Water and steam blanching were found to need lower processing time (1.0 and 1.5 min, respectively) compared with IR (6.0 min) and MW blanching (3.0 min). However, MW‐blanched samples retained higher amounts of ascorbic acid (94.7%). Dry blanching with IR (150C) and MW (17.5 W/g) resulted in higher retention of β‐carotene (103.2 and 118.6%, respectively) compared with water (60.3%) and steam blanching (88.3%). Dry blanching resulted in moisture loss (1–6%) and shrinkage, perhaps resulting in higher shearing force observed in dry blanched slices. Scanning electron micrographs indicated that method of blanching has a role on extent of effect on cell structure. Practical Applications Red bell pepper is a rich source of ascorbic acid and β‐carotene. This study explored the possibilities of dry blanching red bell pepper using infrared and microwave radiation as a potential alternative to water and steam blanching. The dry blanching is expected to retain higher amount of nutrients, reduce solid loss and eliminate effluent generation besides being convenient to operate.